LEAKAGE DETECTION ON THE GALVANIZED IRON PIPELINE USING EMPIRICAL MODE DECOMPOSITION AND HILBERT-HUANG TRANSFORM - M F Ghazali; Gigih Priyandoko (Universitas Mercu Buana, Prodi S2 Teknik Mesin, 2021)
Pipeline networks are one of the most important transportation for gas, oil and water. Leakage in pipelines results in extensive financial loss. To avoid this situation, an algorithm based on the Empirical Mode Decomposition method (EMD) and Hilbert-Huang Transform (HHT) is presented in the research. The objectives of this research to detect pipelines leakage by using EMD method and to locate the location of the leak by using HHT method. The research focuses on the Galvanized Iron (GI) pipe and which the acoustic signal measured by the microphone which act as a sensor is collected by using DASYLab software at frequency of 100 Hz and 500 Hz. It is shown that GI pipe and frequency of 500 Hz produce more accurate results based on the analysis process.